2018
DOI: 10.17219/acem/66806
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of polypropylene and silicone Ahmed® glaucoma valves in the treatment of neovascular glaucoma: A 2-year follow-up

Abstract: Background. Inflammation associated with biomaterials of Ahmed® glaucoma drainage devices may cause the formation of a capsule around the device and can thus have a significant influence on the level of intraocular pressure reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This proved good biocompatibility of silicones was also confirmed in vitro by Windhövel et al who showed low proliferation indices and good cell-repellent properties for six different silicones [26]. Taken together, silicone GDDs demonstrated advantages for IOP control, success rates and fibrosis compared to other materials [3, 23, 25]. In the present study, granulocytes represented a small proportion of the observed inflammatory cells and are most likely part of a secondary reactive process rather than representing an infection at the implant site.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This proved good biocompatibility of silicones was also confirmed in vitro by Windhövel et al who showed low proliferation indices and good cell-repellent properties for six different silicones [26]. Taken together, silicone GDDs demonstrated advantages for IOP control, success rates and fibrosis compared to other materials [3, 23, 25]. In the present study, granulocytes represented a small proportion of the observed inflammatory cells and are most likely part of a secondary reactive process rather than representing an infection at the implant site.…”
Section: Discussionmentioning
confidence: 55%
“…Silicones are often described as biocompatible, being chemically inert and stable [8, 24]. In glaucoma surgery, they show better results than other materials in the IOP control and also regarding the amount of inflammation, fibrin coating and encapsulation [23, 25]. Therefore, most of the GDDs are composed of silicones [3].…”
Section: Introductionmentioning
confidence: 99%
“…The authors compared the clinical outcomes two years after the implantation of polypropylene or silicone Ahmed ® glaucoma valves in patients with neovascular glaucoma. Both materials have a long tradition in glaucoma treatment, but the authors drew attention to the influence of different materials on visual outcomes after Ahmed ® valve implantation for neovascular glaucoma, most likely due to the differences in the biocompatibility of the materials [24].…”
Section: Novel Biomaterials In the Surgical Treatment Of Glaucomamentioning
confidence: 99%
“…It has been shown that a rough surface of an implant leads to increased cell adhesion and, thus, to fibrous encapsulation [16]. Furthermore, polypropylenes and vivathanes seem to be associated with stronger inflammation than silicone [21,23]. Newer studies focus on the opportunity of coating the drainage devices with antiproliferative drugs to avoid postoperative fibrosis [24].…”
Section: Introductionmentioning
confidence: 99%